Cognitive load scale in learning formal definition of limit: A rasch model approach - Rina Oktaviyanthi; Ria Noviana Agus; Mark Lester B. Garcia; Kornkanok Lertdechapat (IKIP Siliwangi and I-MES, 2024)
Constructing proofs for the limit using the formal definition induces a high cognitive load. Common assessment tools, like cognitive load scales, lack specificity for the concept of limits. This research aims to validate an instrument tailored to assess cognitive load in students focused on the formal definition of limits, addressing the need for diverse strategies in education. The research employs a quantitative survey design with a Rasch model approach, utilizing a data collection instrument in the form of a questionnaire. Subsequently, the data are analyzed by focusing on three aspects: (1) item fit to the Rasch model, (2) unidimensionality, and (3) rating scale. A total of 315 students from three private universities in Banten participated as research respondents. The findings of this study affirm the validity of the cognitive load scale centered on the formal definition of limit, meeting the stringent standards set by Rasch modeling. Additionally, the results of the study provide evidence of the scale’s adherence to the monotonic principle of the Rasch model. These outcomes contribute to a comprehensive understanding of cognitive load in the context of learning formal definition of limit, providing a solid foundation for instructional design and assessment strategies.